2019
DOI: 10.15537/smj.2019.2.23904
|View full text |Cite
|
Sign up to set email alerts
|

Factors associated with smoking cessation and smoking cessation interventions in the Gulf Cooperation Council countries

Abstract: Objectives: To examined published literature describing the predictors of smoking cessation (SC) and cessation interventions in Gulf Cooperation Council (GCC) countries. Methods: Systematic literature review using PubMed, Google Scholar, and grey literature. The study was conducted between October and December of 2017. Inclusion criteria were studies reporting factors associated with SC or studies of utilization or delivery of SC medications in GCC countries. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
28
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 22 publications
(28 citation statements)
references
References 23 publications
0
28
0
Order By: Relevance
“…Recently, GCC countries achieved giant steps in the legislation to curb the tobacco epidemic with most countries introducing pictorial warnings and a 100% excise tax on tobacco products, while some countries implemented a plain packaging policy 19 . Nonetheless, more efforts and actions, especially in the area of education of the public and training of healthcare workers 20 , are still required to reverse trends of the smoking epidemic and to overcome challenges. Laws and regulations need to be monitored to ensure firm implementation and prevent interference seeking reversal or attenuation of these regulations.…”
Section: Resultsmentioning
confidence: 99%
“…Recently, GCC countries achieved giant steps in the legislation to curb the tobacco epidemic with most countries introducing pictorial warnings and a 100% excise tax on tobacco products, while some countries implemented a plain packaging policy 19 . Nonetheless, more efforts and actions, especially in the area of education of the public and training of healthcare workers 20 , are still required to reverse trends of the smoking epidemic and to overcome challenges. Laws and regulations need to be monitored to ensure firm implementation and prevent interference seeking reversal or attenuation of these regulations.…”
Section: Resultsmentioning
confidence: 99%
“…patch, inhaler, gum). However, the availability of these smoking alternatives did not increase their utilization because of a lack of social support, costs and access constraints (8). Also, clinicians were not likely to advise patients to quit or use smoking cessation alternatives due to either time constraints with patients or inadequate training in delivering smoking cessation services (8).…”
Section: Introductionmentioning
confidence: 99%
“…A recent systematic review of 21 studies showed that educational programs, clinician -related factors (such as time to provide counseling), and smoking bans were related to smoking cessation among smokers. 23 In a population -based study conducted in Geneva (Switzerland), a significant decrease in the rate of smokers after implementation of a public smoking ban was observed. However, the decrease was only temporal and coincided with a subsequent increase in the number of active smokers.…”
Section: Methodsmentioning
confidence: 99%